Inter-Organizational Professional Networks as Drivers of Career Outcomes and Organizational Performance: Towards the Post-pandemic Horizon - Izabela MARZEC (Communications of International Proceedings, 2022)
The significance of the intangible resources for organizational and individual success results in the necessity to pay attention to employees’ inter-organizational professional networks and their impact on the performance of public organizations and career outcomes of employees. Although this issue has given rise to a great deal of interest in recent years, its empirical studies are still scarce. Therefore, the purpose of this paper is to answer the question: what are the relationships between employee inter-organizational professional networks, employability, career success and organizational performance? This purpose is achieved by presenting the results of a survey carried out in the Polish public organizations. A model of the relationships between these factors was analyzed. In light of the results obtained, interorganizational professional networks emerged as a significant factor influencing employability, intrinsic career success of employees and performance of public organizations.